THE IMPACT OF GOVERNMENT EXPENDITURE ON ECONOMIC GROWTH IN INDONESIA, MALAYSIA AND SINGAPORE - Abdullah, Mahmoud Ahmed; Rusdarti, Rusdarti (Journal of Economic Education, 2017)
Global financial crisis of 2008 led to slowdown of economic growth followed by the decline of global trade volume in the following year. This would  have a negative impact on the reduction of production capacity that could trigger a surge of unemployment rate. In a economy if economic growth increases, government spending will also increased. In Indonesia, Malaysia and Singapore, economic growth that indicated by GDP is different each others, so it will be interesting to analyze the relationship between government expenditure and economic growth.The population in this study are the data for government expenditure, HDI and GDP. While the sample is variable data for government expenditure, HDI and GDP  during the research period, namely 1990-2015. Data collection techniques in this research is the method of documentation. Data analysis techniques using multiple regression analysis to the equation. The model used are secondary data with regression analysis with classic assumption, that are normality test, multicollinearity test, heteroscedasticity and autocorrelation test. The result of this study showed that  there is  impact  of government expenditure on GDP in Indonesia, Malaysia and Singapore. This can be seen from the p-value or significant value that is lower than 0,05 so the hypothesis accepted. Another result showed that there is impact of economic growth on GDP in Indonesia, Malaysia and Singapore. This can be seen from the p-value or significant value that is lower than 0,05 so the hypothesis accepted.Suggestions of this research as follows: For the government, can pay attention on givernment expenditure and economic growth because based on this research affecting GDP in Indonesia, Malaysia and Singapore. For further research, can add another variables that affecting GDP, such as interest rates, kurs, etc.